Efficacy of vocal fold injection of dedifferentiated fat cells in treating glottis closure insufficiency: Insights from a rat model of recurrent laryngeal nerve resection - Ikuo Mikoshiba; Kazuhiro Hagikura; Taro Matsumoto; Tomohiko Kazama; Ryohei Asai; Hiroyuki Hao; Takeshi Oshima (PLoS ONE, 2025)
Glottic insufficiency results from impaired vocal fold contact, leading to a gap between the folds and manifesting as hoarseness and respiratory difficulties. Vocal folds injection is a commonly utilized therapeutic approach to rectify this gap by augmenting vocal folds volume; however, the optimal injectable material remains undetermined. Dedifferentiated fat cells (DFATs), derived from mature adipocytes, exhibit robust proliferative capacity and multipotency, establishing them as potential candidates for treating glottic insufficiency. This study investigated the therapeutic efficacy of DFATs in a rat model of recurrent laryngeal nerve paralysis. Twenty-five rats were used for the therapeutic evaluation: the recurrent laryngeal nerve of each rat was resected unilaterally, and 5 weeks later, the atrophied vocal fold muscles were injected with either 10 μl of saline (control), 1.0 × 106 DFATs in 10 μl (DFAT group), or 1.0 × 106 DFATs combined with 500 ng of basic fibroblast growth factor (bFGF) in 10 μl (DFAT + bFGF group). At 4 weeks post-injection, laryngeal endoscopy evaluated the glottic gap, followed by histological analyses of muscle atrophy, collagen deposition. To investigate mechanisms, an independent cohort of 25 rats received identical treatments and was evaluated 2 weeks post-injection for cell proliferation (Ki-67) and apoptosis (TUNEL). To confirm DFAT engraftment, GFP-labeled DFATs were evaluated at 2, 4, and 6 weeks post-injection. Results indicated that both the DFAT and DFAT + bFGF groups exhibited significantly reduced glottic gaps, increased collagen deposition, and decreased TUNEL-positive apoptotic cells compared to controls. Notably, the DFAT + bFGF group displayed superior outcomes, including a greater vocal muscle area and enhanced Ki-67-positive cell proliferation, indicating reduced atrophy. GFP-positive DFATs remained detectable for up to 6 weeks, confirming engraftment. These findings underscore the potential of DFATs, particularly with bFGF, as an innovative and effective therapy for glottic insufficiency secondary to recurrent laryngeal nerve paralysis.